Microbiology of Industrial, Textile, Domestic and Fish Liquid Waste Treatment (Literature Review) - Nurkayah, Nurkayah; Aseptin Murdini, Lia; Al-laitsi, Mu'awiyatu (Ann Publisher, 2024)
Microbiological research on waste treatment has been conducted to reduce the concentration of waste pollutants, such as ammonia, nitrites, and sulfide acids. Treatment of Fish Washing Waste with Microorganisms Rhodopseudomonas sp., Lactobacillus sp., Aspergillus sp., Penicilium sp., Sacharomyces sp., and Actinomycets sp. to reduce contaminants from cod fish washing waste. The addition of microorganisms can decrease the concentration of ammonia, nitrite, and sulfic acid. Research on the Identification of Organic Pollutant Decomposing Bacteria in Domestic Wastewater found Eschericia coli, Acinetobacter iwoffii, Acinetobacter haemolyticus, Proteus mirabilis, and Pseudomonas sp. The Role of Aerobic Microbes in Liquid Waste Treatment in textile waste treatment, especially in the process of activated sludge ponds found that microbes can reduce the concentration of BOD parameters in textile waste. Bioremediation methods that use microorganism agents can be used to degrade organic materials in waste. Microorganisms have been used to reduce the concentration of waste pollutants, such as ammonia, nitrite, and sulfide acid and microorganisms can be effective in reducing the concentration of waste pollutants.